The association between diet and chronic obstructive pulmonary disease in subjects selected from general practice - Watson, L; Margetts, B; Howarth, P; Dorward, M; Thompson, R; Little, P (The European respiratory journal, 2002)
It is unclear why some smokers develop chronic obstructive pulmonary disease (COPD) whilst the majority do not. Antioxidants found in food may protect against lung tissue injury, but previous epidemiological studies are inconsistent and do not focus on those most at risk of COPD, namely smokers. This case-controlled study measured the difference in dietary intake between smokers and exsmokers with and without COPD. Cases were patients >45 yrs of age with >10 pack-yrs of smoking, a forced expiratory volume in one second (FEV 1 )/forced vital capacity (FVC) of ≤70% and a FEV 1 of ≤80% of predicted. Controls were patients >45 yrs of age with >10 pack-yrs of smoking, a FEV 1 /FVC of >70% and a FEV 1 >80% pred. Data were collected using validated questionnaires. Logistic regression analysis for an unmatched case-controlled study was performed. After controlling for other independent predictors of COPD, those with vegetable intake of ≥1 portion·day −1 (93 g) were less likely to have COPD, as were those consuming ≥1.5 portions·day −1 of fruit. This was not due to an overall reduction in food/calorie intake caused by the disease because: 1) adjusting for body mass index did not alter the estimates; 2) the effect was specific to fruit and vegetables, i.e. not other food groups; and 3) the estimates from incident cases were similar. In conclusion, fruit and vegetable consumption is inversely associated with chronic obstructive pulmonary disease and may explain why some smokers do not develop chronic obstructive pulmonary disease.